2009
DOI: 10.1007/s11832-009-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus non-operative management of pediatric medial epicondyle fractures: A systematic review

Abstract: PurposeThere is ongoing debate about the management of medial epicondyle fractures in the pediatric population. This systematic review evaluated non-operative versus operative treatment of medial epicondyle fractures in pediatric and adolescent patients over the last six decades.MethodsA systematic review of the available literature was performed. Frequency-weighted mean union times were used to compare union rates for closed versus open treatments. Moreover, functional outcomes and range-of-motion variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 111 publications
5
64
1
4
Order By: Relevance
“…Non-operative measures commonly produce satisfactory results and return to play 1–3 6 18 19 24 26–30. However, despite evidence of satisfactory results of non-operative treatment, there has been an increasing trend in operative treatment for physeal elbow injury 31. Particularly for athletes, there remains a theoretical advantage of operative management in achieving bony union, given the heavy demand on the dominant elbow 31.…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative measures commonly produce satisfactory results and return to play 1–3 6 18 19 24 26–30. However, despite evidence of satisfactory results of non-operative treatment, there has been an increasing trend in operative treatment for physeal elbow injury 31. Particularly for athletes, there remains a theoretical advantage of operative management in achieving bony union, given the heavy demand on the dominant elbow 31.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits include early postoperative range of motion, early return to sports, 100% union rate, and excellent recovery of preoperative range of motion. 1,7 Theoretically, the washer increases the surface area for compression, improves stability, and prevents the screw head from penetrating or fragmenting the apophyseal epicondyle fragment. However, adding the washer also prevents the ability of the surgeon to bury the screw head, which can be done in the absence of the washer, potentially leading to hardware prominence.…”
Section: Discussionmentioning
confidence: 99%
“…1 The treatment of displaced medial epicondyle fractures in children remains controversial due to the lack of high-level evidence, however, good results have been reported with both operative and nonoperative management. [2][3][4][5][6][7][8][9][10][11][12] For elbows that are treated surgically, the goal is to achieve anatomic reduction with adequate fracture fixation to allow for early postoperative mobilization to minimize postoperative stiffness.…”
mentioning
confidence: 99%
“…1,2 There are absolute indications for operative management, including an open fracture or an entrapped intra-articular fragment, 3,4 as well as relative indications, including: valgus instability, ulnar neuritis, and various amounts of fragment displacement. 5 The hypothesis for recommending surgery when a fragment is displaced is that a displaced fragment may result in pain, instability, nonunion, and muscle weakness. 3,4 Historical publications over the past 50 years have suggested that the primary displacement vector is medial, as measured on the anteroposterior (AP) radiographs, 1-8 and many authors have proposed a variety of thresholds for acceptable measures, ranging from 2 mm to 2 cm of medial displacement.…”
mentioning
confidence: 99%
“…3,4 Historical publications over the past 50 years have suggested that the primary displacement vector is medial, as measured on the anteroposterior (AP) radiographs, 1-8 and many authors have proposed a variety of thresholds for acceptable measures, ranging from 2 mm to 2 cm of medial displacement. [3][4][5] However, it is unclear whether AP radiographs measuring medial displacement are accurate reflections of the true anatomic fragment displacement. Interobserver agreement for measurements of medial displacement is only 46%.…”
mentioning
confidence: 99%